2009
DOI: 10.1159/000280584
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Organogenesis in Mammals: Mice Cannot Tell Us Everything

Abstract: The mammalian ovary shows extensive variation mainly in relation to the interstitial tissue of the ovary, the so-called interstitial gland, and the degree of gonad regionalisation, which implies the existence of a cortex and a medulla. Three mammalian species, mouse, human, and mole, have been reviewed here as representative animal models for ovarian variability. Whereas the human ovary may be considered to have a conventional pattern of development, the mouse and the mole represent the two extremes of the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
2
29
0
2
Order By: Relevance
“…In situ hybridization studies showed that miR-124 is present mainly in the cortical region of the female gonad at 13.5 dpc (i.e., the portion from which the ovarian tissue mostly develops in mammals and other vertebrates [48] and also the region in which the complete inhibition of Sox9 would be especially necessary in the differentiating female gonad. The fact that Sox9 is expressed mainly in the medulla of the developing testis is not a valid argument against this hypothesis because this is not the case in developing ovaries, where Sry is absent and, thus, Sox9 is not up-regulated anywhere.…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization studies showed that miR-124 is present mainly in the cortical region of the female gonad at 13.5 dpc (i.e., the portion from which the ovarian tissue mostly develops in mammals and other vertebrates [48] and also the region in which the complete inhibition of Sox9 would be especially necessary in the differentiating female gonad. The fact that Sox9 is expressed mainly in the medulla of the developing testis is not a valid argument against this hypothesis because this is not the case in developing ovaries, where Sry is absent and, thus, Sox9 is not up-regulated anywhere.…”
Section: Discussionmentioning
confidence: 99%
“…The ovary in many species, including most vertebrates, is regionalized into a highly vascularised medulla and a cortical region in which the germ cells reside [67]. In mouse, this regionalization is not obvious at a morphological level until shortly before birth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mice with inducible gonad-specific Cre recombinases should permit the re-examining of the previously known genes that have already been implicated in sexual development, for example, in cases where the null phenotypes show defects in gonad formation, rather than subsequent sexual differentiation. Still, even the most ardent murine aficionado has to keep the perspective that mice cannot tell us everything about ovarian organogenesis in other species, including humans [Jimenez, 2009]. Here too, whole genome sequencing technologies are bound to uncover novel sex determination genes in patients with DSD [Arboleda and Vilain, 2011].…”
Section: Discussionmentioning
confidence: 99%